ANALISIS FAKTOR-FAKTOR KESULITAN BELAJAR SISWA PADA MATA PELAJARAN IPA BIOLOGI KELAS VII SMP NEGERI 4 AMANDRAYA - Alfrilyani Ndruru (TUNAS : Jurnal Pendidikan Biologi, 2023)
Learning difficulty is a condition in which the competence or achievement achieved does not match the standard criteria that have been set, either in the form of attitudes, knowledge or skills. The purpose of this research is to describe students' learning difficulties in Science- Biology material in class VII SMP Negeri Amandraya 2021 academic year / 2022, To find out what are the factors that cause learning difficulties in Science- Biology material in class VII SMP Negeri 4 Amandraya in the 2021/2022 academic year, To find out solutions in overcoming students' learning difficulties in Science- Biology material in class VII SMP Negeri 4 Amandraya In the 2021/2022 academic year, the type of research used is qualitative research with a descriptive approach that describes the existing data. The data source in this study were 27 students at SMP Negeri 4 Amandraya Class VII, consisting of 16 boys and 11 girls. . Data collection techniques, namely by interviewing documentation, and distributing questionnaires. In accordance with the results of the interviews that the researchers conducted, the results of testing in this study were student learning difficulties, namely the lack of focus and concentration in student learning caused by internal factors and external factors. Based on the results of research that has been carried out by researchers regarding the analysis of the factors of student learning difficulties in Biology Science class VII SMP Negeri 4 Amandraya. It can be concluded that the factors of student learning difficulties are influenced by factors from themselves, factors from family, factors from school, and factors from the community environment. From the results of this study the researcher gave suggestions that there must be cooperation between parents and schools in educating and motivating students in teaching, and paying attention to student learning developments.